A solar activity correction term for the IRI topside electron density model. Issue 5 (1st September 2021) - Bilitza, Dieter; Xiong, Chao
Abstract: In situ measurements by the Low Earth Orbital (LEO) satellites, such as CHAMP, GRACE, and C/NOFS satellites have shown that the International Reference Ionosphere (IRI) model has shortcomings in describing the solar activity variation of the topside electron density. In particular IRI overestimates the measured densities in the topside ionosphere during the very low solar activity reached during the last solar minimum (2008–2009). We have used Alouette and ISIS topside sounder data and CHAMP, GRACE, as well as Swarm in situ measurements to deduce a correction term for the IRI electron density topside model that more accurately describes the variation with solar activity. We have used a linear variation with the solar index PF10.7 and described the latitudinal and altitudinal variation of the regression parameters A0 and A1 (intercept and slope). We find good agreement between the regression parameters deduced from the topside sounder and from the CHAMP and GRACE observations. Swarm results show the same latitudinal structure as the other data sets, however, a scaling factor is needed to obtain agreement of the absolute values. The new model was evaluated with Alouette and ISIS topside sounder, as well as LEO satellites in situ data showing a significant improvement over the current IRI model.